Genome sequencing analysis reveals virulence-related gene content of Ochrobactrum intermedium strain 229E, a urease-positive strain isolated from the human gastric niche - Kulkarni, Girish J.; Shetty, Sudarshan; Dharne, Mahesh S.; Shouche, Yogesh S. (Fems Microbiology Letters, 2014)
We report draft genome sequence of Ochrobactrum intermedium strain 229E concurrent with Helicobacter pylori in urease positive gastric biopsy of non-ulcer dyspeptic individual from Southern part of India. Since the role of Ochrobactrum in human gastric environment is poorly understood, comprehensive pathological, microbiological, and genome level understanding are necessary to evaluate its association with H. pylori in the gastric niche. Comparative analysis of O. intermedium 299E strain revealed functional similarities with virulence related gene clusters present in H. pylori genomes, which probably might aid in its ability to persist in the human gastric mucosa. However, H. pylori specific vacuolating cytotoxin (vacA) involved in vacuolization, cytotoxicity, and T-cell inhibition was absent in the O. intermedium 229E genome. Taken together, O. intermedium 229E shared numerous features like secretion system, urease, and flagella with H. pylori genome sequence that might aid concurrence in the gastric niche.
Keywords: Helicobacter pylori; Ochrobactrum intermedium strain 229E; virulence related gene clusters